Social Workers’ Interest in Building Individuals’ Financial Capabilities - Mathieu R Despard; Gina A N. Chowa (Journal of Financial Therapy, 2010)
Social workers have many opportunities to integrate a focus on personal finance into their practice with mostly lower-income and vulnerable client populations. However, little is known about social workers’ interest in personal finance. Results of a survey of social workers (N = 56) interested in integrating personal finance content into their practice are reported in this paper. Ways in which social workers might further develop knowledge and skills in personal finance are discussed. Professional perspectives that social workers may lend to inform financial education and counseling and the emerging field of financial therapy are also explored. Social workers can offer an understanding of the environmental risks that affect the financial health of low-income individuals and families and resources that can help build financial capability.
Keywords: social work; financial planning; financial therapy